Vocational Education Management: Multi-Case Study at SMK Center of Excellence Bitung City, Manado City, Tomohon City North Sulawesi Province - Punuh, Grace; Katuuk, Deitje Adolfien; Rawis, Joulanda A.M.; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
The research in this dissertation is motivated by a phenomenon where there are still various challenges in the development and efforts to advance Vocational High Schools which include: the still high unemployment rate for Vocational High School graduates, and incomplete integration between Vocational High Schools and the industrial world/world of work such as: development curriculum, learning process, learning evaluation, to graduate marketing. The focus of the research in writing this thesis is: 1) How is Vocational Education Planning at Christian Vocational School 2 Tomohon, SMKN 2 Bitung and SMKN 1 Manado? 2) What is the Implementation of Vocational Education at Christian Vocational Schools 2 Tomohon, SMKN 2 Bitung and SMKN 1 Manado? 3) How is the Monitoring and Evaluation (Monev) of Vocational Education at Christian Vocational Schools 2 Tomohon, SMKN 2 Bitung and SMKN 1 Manado? This type of research is a qualitative descriptive study using a multi-case approach, data collection techniques 1) Participant Observation, 2) In-depth interviews, 3) Documentation, 4) FGD (Focus Group Discussion), and data analysis with the approach of (1) analysis of individual case data, and (2) cross-case analysis of data. From the results of this study, the authors conclude that: 1) Vocational Education Planning: the principal prepares the documents needed for registration SMK-PK and forms an SMK-PK team and a development team involving related stakeholders. 2) Implementation of Vocational Education: The implementation of the SMK-PK program starts in 2021 which is SMK-PK in the first stage the school gets assistance in the form of physical equipment, while in the second stage, it focuses on the program. The principal participates in every program or activity carried out such as collaboration with du/di, participates in the process of teaching and learning activities, and so on. 3) Monitoring and Evaluation (Monev) of Vocational Education: The school principal conducts internal evaluations related to the curriculum program and management of SMK-PK. The Principal also evaluates the learning process by controlling the implementation of the learning process. In the management of SMK-PK, there is also an evaluation in the form of control carried out by the government on the management of SMK PK funds so that schools must report regarding the progress of program implementation and the use of SMK-PK funds.